2014
DOI: 10.1038/pj.2014.92
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation behavior in water of amphiphilic diblock copolymers bearing biocompatible phosphorylcholine and cholesteryl groups

Abstract: Poly(2-(methacryloyloxy)ethyl phosphorylcholine)-block-poly(cholesteryl 6-methacryloyloxyhexanoate) (PMPC 82 -b-PChM n ) copolymers with different PChM block lengths were prepared via reversible addition-fragmentation chain transfer controlled/living radical polymerization using a PMPC-based macro-chain transfer agent. The subscript number and n ( = 3 and 6) refer to the degree of polymerization of the PMPC and PChM blocks, respectively. PMPC 82 -b-PChM n cannot dissolve in water directly due to the strong hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1b , right). Previous studies suggest that the methyl group is highly hydrophobic, and hydrophobic forces are indeed vastly involved in aggregation processes of polymers 16 . Moreover, hydrophobic driven methylation-dependent conformational changes of DNA have already been reported in the literature 12 .…”
Section: Resultsmentioning
confidence: 98%
“…1b , right). Previous studies suggest that the methyl group is highly hydrophobic, and hydrophobic forces are indeed vastly involved in aggregation processes of polymers 16 . Moreover, hydrophobic driven methylation-dependent conformational changes of DNA have already been reported in the literature 12 .…”
Section: Resultsmentioning
confidence: 98%
“…Recent progress in the development of controlled/living polymerization methods such as atom transfer radical polymerization (ATRP) and reversible addition–fragmentation transfer (RAFT) polymerization has facilitated the design of a wide range of well-defined controlled-structure polymers. Many examples of well-defined PMPC-based diblock copolymers have been prepared by ATRP , and RAFT. , Of particular relevance to the present study, (1-ethoxy­carbonyl)­vinyl dimethyl­phosphate was homopolymerized via ATRP and also copolymerized using either polystyrene or poly­(methyl methacrylate) macroinitiators . While control over the polymerization of this dialkylphosphate monomer was rather poorincomplete conversions or broad molecular weight distributions ( M w / M n > 1.60) were obtained depending on the choice of catalystsubsequent hydrolysis produced the corresponding phosphoric acid-based diblock copolymers.…”
Section: Introductionmentioning
confidence: 92%
“…Many examples of well-defined PMPC-based diblock copolymers have been prepared by ATRP 25,26 and RAFT. 27,28 Of particular relevance to the present study, (1-ethoxycarbonyl)vinyl dimethylphosphate was homopolymerized via ATRP and also copolymerized using either polystyrene or poly(methyl methacrylate) macroinitiators. 29 While control over the polymerization of this dialkylphosphate monomer was rather poorincomplete conversions or broad molecular weight distributions (M w /M n > 1.60) were obtained depending on the choice of catalystsubsequent hydrolysis produced the corresponding phosphoric acid-based diblock copolymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was revealed that the exterior of the agglomerated DNAs has significant variations, while the inside component is relatively stiff (see Figure c,d). It is worth noting that the methylated DNA shows a larger rigid region (shown in orange) in comparison to the unmethylated DNA, which is due primarily to the methylation-dependent hydrophobicity. , The hydrophobic forces have been found to be related to polymer aggregation . Our results demonstrate that the DNA polymeric behavior is strongly affected by DNA methylation, leading to significant differences in DNA solvation and DNA–gold affinity between the methylated and unmethylated DNA, discussed in the following sections.…”
Section: Resultsmentioning
confidence: 60%
“…16,43 The hydrophobic forces have been found to be related to polymer aggregation. 44 Our results demonstrate that the DNA polymeric behavior is strongly affected by DNA methylation, leading to significant differences in DNA solvation and DNA−gold affinity between the methylated and unmethylated DNA, discussed in the following sections.…”
Section: Self-assembly Of Methylated Dna In Aqueousmentioning
confidence: 64%